Ernest Hambloch and Borges: presidentialism and modereting power in Brazil - Nunes, Edson Correa (Laboratório Editorial Faculdade de Ciências e Letras, 2015)
This paper will seek to equate the criticisms of Brazilian presidentialism by two authors: Ernest Hambloch and Borges de Medeiros, who deal with the institutional causes that underlie the authoritarian character of our political regime. For both, the reform of the political system is the fundamental demand; however, their proposals suggest different ways: parliamentarianism and presidentialism with moderating power. Thus, in dialogue with these authors, we will try, from its contextual political trajectories, understand their views and most fundamental diagnosis and the different proposals correction for distortions of imperial presidentialism in Brazil.